Advanced Engineering of Materials Through Lasers - Radhakrishnan, J.; Pathak, Sunil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book covers the fundamentals of different laser-based manufacturing and processing, namely laser shock peening, laser micromachining, laser cleaning, cladding, remelting, laser honing, and other several aspects of lasers. The book discusses the general laser interaction with different materials. The application of laser-based post-processing of additive manufacturing and repair engineering is reported. It also provides the reader with mechanism of lasers in manufacturing and recent developments in tools, technologies, controls, and operations.
Introduction to Lasers and Processing's of Materials -- Introduction to Gas and Solid State Laser Techniques in Cutting Process -- Laser Cutting of Ceramic Matrix Composites -- Laser shock Peening: A walkthrough -- Laser Re-melting of Atmospheric Plasma Sprayed High Entropy Alloy -- Surface Morphology of Nimonic Alloy 263$1!" (Bin Nanosecond Pulsed Laser Ablation -- Laser-based Post-processing of Metal Additive Manufactured Components -- Advances in Superhydrophobic Surfaces: Biology to Biomimetic -- Index.s
Keywords: Materials; Lasers; Materials Engineering; Laser Technology; Lasers -- Industrial applications; Metallurgy -- Laser use in